UJI DAYA HASIL BEBERAPA VARIETAS JAGUNG TERHADAP PAKET PEMUPUKAN ORGANIK, ANORGANIK DAN PUPUK HAYATI MIKORIZA - Muhajir, Muhamad; Astiko, Wahyu; Abdurachman, Hanafi (CROP AGRO, Scientific Journal of Agronomy, 2023)
The corn food commodity is one of the leading commodities of West Nusa Tenggara. In addition, NTB is also one of the target areas for increasing national maize production. This study aims to determine the yield yield of several varieties of maize given a mixed package of organic, inorganic and mycorrhizal fertilizers. This research was conducted from May to August 2020 in Midang Village, Gunung Sari District, West Lombok Regency, Microbiology Laboratory and Soil Physics and Chemistry Laboratory, Faculty of Agriculture, Mataram University. The method used in this study was a randomized block design with 5 treatments, namely V1 (P8IS variety), V2 (P8DPP variety), V3 (Gumarang variety), V4 (Lamuru variety), V5 (Sukmaraga variety). Each treatment was repeated 3 times in order to obtain 15 experimental plots. The results showed that maize varieties given organic, inorganic and mycorrhizal fertilizers had a significant effect on growth, yield of maize, nutrient status and nutrient uptake, number of mycorrhizal spores and root colonization by mycorrhizae. Sukmaraga variety has better growth and yield than other varieties, this is reflected in the growth parameter indicators and yield parameter indicators, namely harvest dry ear weight per plant (271.5 g), dry ear weight per plant (255 g), length ear (16.5 cm), ear diameter (5.3 cm), seed dry weight per plant (180 g), and weight 1000 seeds (288 g).